Water extract of Clinacanthus nutans leaves exhibits in vitro, ex vivo and in vivo anti-angiogenic activities in endothelial cell via suppression of cell proliferation - Chin Theng Ng; Lai Yen Fong; Jun Jie Tan; Nor Fadilah Rajab; Faridah Abas; Khozirah Shaari; Kok Meng Chan; Fariza Juliana; Yoke Keong Yong (BMC, 2018)
Abstract Background Clinacanthus nutans (Burm. f.) Lindau. has traditionally been using in South East Asia countries to manage cancer. However, scientific evidence is generally lacking to support this traditional claim. This study aims to investigate the in vitro, ex-vivo and in vivo effects of C. nutans extracts on angiogenesis. Methods C. nutans leaves was extracted with 50-100% ethanol or deionised water at 1% (w/v). Human umbilical veins endothelial cell (HUVEC) proliferation was examined using MTT assay. The in vitro anti-angiogenic effects of C. nutans were assessed using wound scratch, tube formation and transwell migration assays. The VEGF levels secreted by human oral squamous cell carcinoma (HSC-4) cell and HUVEC permeability were also measured. Besides, the rat aortic ring and chick embryo chorioallantoic membrane (CAM) assays, representing ex vivo and in vivo models, respectively, were performed. Results The MTT assay revealed that water extract of C. nutans leaves exhibited the highest activity, compared to the ethanol extracts. Therefore, the water extract was chosen for subsequent experiments. C. nutans leaf extract significantly suppressed endothelial cell proliferation and migration in both absence and presence of VEGF. However, the water extract failed to suppress HUVEC transmigration, differentiation and permeability. C. nutans water extract also did not suppress HSC-4 cell-induced VEGF production. Importantly, C. nutans water extract significantly abolished the sprouting of vessels in aortic rings as well as in chick embryo CAM. Conclusion In conclusion, these findings reveal potential anti-angiogenic effects of C. nutans, providing new evidence for its potential application as an anti-angiogenic agent.